Determination of Nitazoxanide in Biological Matrices by LC-MS/MS Technique: Method Development and Validation - Mohammad, Abdul Saleem; Jayanthi, B (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Determination of pharmaceuticals in the biological matrices is essential for toxicologic and pharmacokinetic applications. The main objective of the current work was to develop a bioanalytical method for quantifying nitazoxanide in biological samples by LC-MS/MS. Materials and Methods: Chromatographic elution of nitazoxanide and linagliptin were achieved on C18-hypersil (5 μ, 50x4.6mm) stationary phase with mobile phase consisting of acetonitrile and 0.1% HCOOH (75:15, v/v) processed at 0.8 ml/min flow rate. Linagliptin was utilized as an internal standard (IS). Results: The method was linear in the concentration levels of 0.53–21.2 ng/ml with more than 0.999 r2 values, consisting of 0.53 ng/ml as the lower limit of quantification (LLOQ). Analytes were subjected to pretreatment by liquid-liquid extraction (LLE) procedure with average extraction recovery findings within 99.93±5.04%. Method accuracy findings were present in between 96.44% to 104.31%, and the assessed percentage relative standard deviation findings for within and between run precision were ≤ 4.68%. Conclusion: The developed LC-MS/MS procedure for quantitating nitazoxanide in the biological matrix was suitable for routine analysis of patients’ blood samples for pharmacokinetic studies and drug monitoring.
Keywords: Nitazoxanide; Antiviral; LC-MS/MS; Validation; Accuracy